A Composite Membrane of Caesium Salt of Heteropolyacids/Quaternary Diazabicyclo-Octane Polysulfone with Poly (Tetrafluoroethylene) for Intermediate Temperature Fuel Cells - Xu, Chenxi (MDPI, 2012)
Inorganic-organic composite electrolyte membranes were fabricated from CsXH3−XPMo12O40 (CsPOMo) and quaternary diazabicyclo-octane polysulfone (QDPSU) using a polytetrafluoroethylene (PTFE) porous matrix for the application of intermediate temperature fuel cells. The CsPOMo/QDPSU/PTFE composite membrane was made proton conducting by using a relatively low phosphoric acid loading, which benefits the stability of the membrane conductivity and the mechanical strength. The casting method was used in order to build a thin and robust composite membrane. The resulting composite membrane films were characterised in terms of the elemental composition, membrane structure and morphology by EDX, FTIR and SEM. The proton conductivity of the membrane was 0.04 S cm−1 with a H3PO4 loading level of 1.8 PRU (amount of H3PO4 per repeat unit of polymer QDPSU). The fuel cell performance with the membrane gave a peak power density of 240 mW cm−2 at 150 °C and atmospheric pressure.